PELAYANAN UMAT: PELAYANAN YANG BERBASIS DATA - Gegel, I Ketut (STIPAS TAHASAK DANUM PAMBELUM KEUSKUPAN PALANGKARAYA, 2016)
The writer argues that pastoral means placing the interests of the people as the first of any interests. In line with that, the pastoral choice must be oriented to meet the people needs in accordance with the circumstances of its time. We need to conduct social analysis in the form of data collection, both at parish and diocese level in order to find out what is the real interest of the people. In this perspective, data-based pastoral is the answer to a pastoral pattern based on and for the people.